Global trend of ethnomathematics studies of the last decade: A bibliometric analysis - Deda, Yohanis Ndapa; Disnawati, Hermina; Tamur, Maximus; Rosa, Milton (Jurnal Infinity, 2024)
This study aims to investigate ethnomathematics research trends through bibliometric analysis on widely distributed Google Scholar (GS) and Scopus databases. One thousand seventy-seven papers were reviewed from GS and Scopus databases searched using Harzing's Publish on 9 January 2023. A descriptive study approach was used to investigate the data. The result of this study is that the number of ethnomathematics studies has increased over the last decade (2012-2022). The most productive author based on GS is Rosa from Brazil, and the full author based on Scopus is Widada from Indonesia. The principal authors with the highest citations are Ascher, based on GS, and Muhtadi, based on Scopus, with the highest citations. The Journal of Physics: Conference Series (JPCS) in the last decade is the most crucial source of ethnomathematics documents. Based on VosViewer visualization, Rosa is the author who has the most co-authorship papers and total link strength. The VosViewer displays four clusters related to Ethnomathematics: mathematics education, skills, ethnomathematics studies, and geometry. Our strong recommendations regarding this study are ethnomathematics research related to literacy, numeracy, technocracy, and mathematical abilities. The results can assist relevant researchers in understanding trends in ethnomathematics research and recommend guidelines for other studies.